Physiological changes in newborn skin after natural oil massage in rural Nepal - Marty O Visscher; Aimee Summers; Vivek Narendran; Subarna K Khatry; Jeevan B Sherchand; Steven C LeClerq; Joanne Katz; James M Tielsch; Luke C Mullany (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Natural oils are applied daily to newborn infant skin during massage in certain cultures. In hospitalized premature infants, topical oils reduced infection and improved skin condition. A community study among neonates in rural Nepal compared sunflower and mustard oils for effects on skin integrity. Particularly notable was the rapid increase in skin rash that peaked at day 14 and lessened by day 28 for both oils, a finding not previously reported. # Methods To investigate the rash physiology, high-resolution digital images were collected for a subset of 216 premature and full-term infants. Image features were characterized for type and severity, quantified for color and surface texture and compared to measures of skin barrier integrity. # Results Skin features were observed in 403 of 811 images, including localized erythema, discrete papules and an occasional pustule. Miliaria crystallina was noted in 32.2%. A second texture, with raised, "pebble" features, characterized 26%. Of 216 subjects, 61% had "pebble" on at least one visit. Miliaria severity increased and day 14 was higher than 1 and 7 (P<0.05). Pebble texture severity increased. Day 28 was higher than 1, 3 and 7 (P<0.05). Skin pH was lower and erythema, rash and massage numbers were higher for miliaria than without it (P<0.05). Subjects with and without pebble texture did not differ for skin integrity measures. # Conclusions An understanding of the maturational changes in qualitative and quantitative skin color and texture with routine neonatal oil massage provides the basis for leveraging this commonly practiced ritual to optimize skin care.